Normative Legal Models of Administrative Expulsion: a Comparative Legal Research - Oleg N. Sherstoboev (Сибирское юридическое обозрение, 2016)
Different countries solve issues of grounds and procedure for the expulsion of foreign nationals outside the country in their own way. However, modern countries gradually unify their regulatory legal models of expulsion. This is due to the impact of generally accepted international norms and principles, as well as the identical problems associated with finding a large number of immigrants. Conducted comparative study have shown that the expulsion of foreigners considered by the official authorities of the various states as an integral part of the sovereign powers aimed at protecting their own legal order.